Reforms in the regions are the main driver of sustainable development and improving the wellbeing and economic status of the population as an example of the Republic of Uzbekistan. - Ahmedov Tursun Muhitovich; Tursunova Nazokat Tolibjonovna (Academia One Publishing, 2024)
Reforms at the regional level, through addressing disparities, promoting localized solutions, fostering economic diversification, enhancing regional competitiveness, and supporting environmental sustainability, are critical to driving sustainable development and improving the well-being and economic status of the populace. The article presents the author's understanding of the role of reforms in Uzbekistan by indicating the reasonable facts based on Strategy “Uzbekistan-2030”
Keywords: Regional reforms; sustainable development; well-being